LD Body in Epitrochliar Lymphnode in a Bone Marrow and Splenic Aspiration Negative Indian Kala Azar - Das Gupta, Ratan; Das, Aparna; Miah, Titu; Imran Khan, Mohammad Ashik; Hasnain, Muntasir; Alam, Billal; Kabir, Ahamedul (Journal of Medicine, 2011)
Kala Azar is a parasitic disease cause by Leishmania Donovani, transmitted by sand fly phlebotomus. Lymphadenopathy is not a common presentation in Indian Kala azar. We present an adult male from endemic zone of kalaazar presented with epitrochlear lymphadenopathy and hepato-splenomegaly and diagnosed by presence LD in lymphnode biopsy. Keyword: Kala Azar, Lymphadenopathy, Leishmania Donovani (LD) body, Bangladesh DOI: http://dx.doi.org/10.3329/jom.v12i2.8429 JOM 2011; 12(2): 188-190